2010
DOI: 10.1161/atvbaha.110.203356
|View full text |Cite
|
Sign up to set email alerts
|

CCN3 Inhibits Neointimal Hyperplasia Through Modulation of Smooth Muscle Cell Growth and Migration

Abstract: Objective-CCN3 belongs to the CCN family, which constitutes multifunctional secreted proteins that act as matrix cellular regulators. We investigated the pathophysiological roles of CCN3 in the vessels. Methods and Results-We examined the effects of CCN3 on the proliferation and migration of rat vascular smooth muscle cells (VSMC). CCN3 knockout mice were created, and vascular phenotypes and neointimal hyperplasia induced by photochemically induced thrombosis were investigated. CCN3 suppressed the VSMC prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 34 publications
6
74
0
Order By: Relevance
“…Indeed, two reports describing the phenotype of NOV 2/2 mice revealed that they are viable and apparently normal and fertile (22,40). However, after a lesion of the femoral artery, the null mice presented an enhancement of neointimal thickening compared with WT mice during vascular repair (22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, two reports describing the phenotype of NOV 2/2 mice revealed that they are viable and apparently normal and fertile (22,40). However, after a lesion of the femoral artery, the null mice presented an enhancement of neointimal thickening compared with WT mice during vascular repair (22).…”
Section: Discussionmentioning
confidence: 99%
“…Mice genotypes were performed as previously described (22). The genotypes were further checked by NOV mRNA levels in epididymal white adipose tissue (eWAT) and subcutaneous WAT (scWAT), the plasma level of the protein and its expression in heart where NOV is normally highly expressed ( Supplementary Fig.…”
Section: Novmentioning
confidence: 99%
See 1 more Smart Citation
“…Knockdown of CCN1 by siRNA inhibits neointimal hyperplasia after balloon angioplasty (Matsumae et al, 2008). CCN3 could inhi-bit neointimal hyperplasia through modulation of SMC growth and migration (Shimoyama et al, 2010). According to their structural similarity, we speculated that CCN4 may play a role in cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that CCN3 can affect vascular function by regulation of endothelial cell inflammation and neointimal hyperplasia (Lin et al 2010;Shimoyama et al 2010). CCN3 knockout mice are viable and develop to adulthood with a normal vasculature and ECM composition (Shimoyama et al 2010). CCN4 (WISP1) was initially identified as a gene in a mouse mammary epithelial cell line (Pennica et al 1998) with later studies restricting CCN4 protein expression to osteoblast and osteoblastic progenitor cells during development and bone fracture repair (French et al 2004).…”
Section: Role Of Ccns In Vascular Development and Homeostasismentioning
confidence: 99%